Analysis of completeness of information in package inserts of Indian and foreign multinational pharmaceutical companies: an Indian perspective - ., Vikas; Gupta, Mahesh Chander (International Journal of Basic & Clinical Pharmacology, 2020)
Background: A package insert (PI) should contain all the information required for safe and effective use of the medicine. The present study evaluated and compared the completeness of information in package inserts of Indian and foreign multinational pharmaceutical companies based in India. Methods: A total 150 PI’s consisting of 75 package inserts of Indian and foreign multinational pharmaceutical companies in India were collected and analyzed based on the criteria of Indian drugs and cosmetics rules, 1945 under section 6.2, 6.3 of schedule D, which consists of 25 parameters. Each criteria was scored for presence of information as ‘1’, absence as ‘0’. Total score was 25, score >20 was graded as ‘A’, 10-20 as ‘B’ and <10 as ‘C’. Data was expressed as numbers and percentage. Results: Total 150 PI evaluated included antimicrobials, antipsychotics etc. Out of all the PIs 26% belonged to grade A, 70% belonged to grade B and 4% belonged to grade C. Lack of information was found in both the categories of PIs. Foreign PIs performed better in comparison to Indian PIs as in grade A, 27 out of 41 PIs were foreign whereas 56 PI’s in grade B were Indian and 47 were foreign. Both categories of PI showed good information about active ingredient, dosage form, warnings, contraindications and lacked information about retail price and references etc. Conclusions: Both categories of PIs were deficient in completeness of information. The pharmaceutical companies, both national and foreign, must provide the information as per regulatory norms.